Project Planning Practices in State Tourism Corporations - Singh, Manjit (Gyan Management Journal, 2007)
It is on record that a major factor in inadequate performance of enterpri es in lndia ha· been poor quality of investment J cision · in both the private and public sectors of the economy. While identifying new project<;, political parties in India have the considera ion of political gains only.Thei. motivation to und 1take proj cts is always political. They endeavour to please a particular con tituent to gamer its support. Tourjsm sector is no exc ption